Exploring Effects of Uncertainty Avoidance in Self-Service Technology User Interface Design in Japan and Finland - Mäkipää, Juho-Pekka; Rousi, Rebekah; Vartiainen, Tero (IOS Press, 2025)
Geert Hofstede famously labelled culture as the “software of the mind”, affecting how people cognitively process the world, and how organisations, communities and societies are structured. This lends to explain how culture influences the ways that people, perceive, use and experience technology design, and how within user experience design, cultural logic should be applied to develop user interfaces (UI). This study draws on Hofstede’s cultural dimension of ‘uncertainty avoidance’ (UA) to examine how UA, or the ways in which people within certain cultures cope with uncertainty, unknown and change, to examine the influence of culture on self-service technology (STT) UI design. The authors evaluate a sample of ten UIs from various STTs in Japan, a country of higher UA (N = 5), and Finland (N = 5) a country of lower UA. The results show that in higher UA cultures design of STT’s UI often rely on multimodal interaction, bright colours, and clear progress guidance via illustrations. However, we find also some contradictions in design solutions within the same cultures. It seems that instead of designers’ cultural identities playing a role, designers’ expertise in usability, company brand, and requirements by context affect how UI components are constructed. We discuss theoretical impacts of these manifestations of UI design on how they relate to accessibility and usability. As an implication to the practice, we propose a UI design assumption that embraces ‘Zero Uncertainty’, combining clear flow guidance, text and illustrations, with multimodal guidance and feedback.
Keywords: Cross-cultural research; Cultural dimensions; Uncertainty avoidance; Self-service technologies; User interface design; Zero uncertainty; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Viestintätieteet|en=Communication Studies|